Criteria and indicators for sustainable plantation forestry in Indonesia - Muhtaman, D.R.; Siregar, C.A.; Hopmans, P. (Center for International Forestry Research, 2000)
CIFOR has developed a system for testing criteria and indicators to assess the sustainability of management of natural forests at the level of the forest management unit. This system was used to develop and test C&I for industrial plantation concession areas in Sumatra and Kalimantan. The C&I for plantations have a strong focus on forest management and environment impacts. But for long-term sustainability of plantation forestry, it is more related to social rather than management or environmental issues. It is also suggested that C&I on legal and institutional arrangements be included, and government agencies responsible for plantation development be involved as stakeholders in the process.